You play the girl: on Playboy bunnies, Stepford wives, train wrecks, and other mixed messages - Chocano, Carina (Houghton Mifflin Harcourt, 2017)
"Who is "the girl"? Look to movies, TV shows, magazines, and ads and the message is both clear and not: she is a sexed-up sidekick, a princess waiting to be saved, a morally infallible angel with no opinions of her own. She's whatever the hero needs her to be in order to become himself. She's an abstraction, an ideal, a standard, a mercurial phantom. In You Play the Girl, Chocano blends formative personal stories with insightful and emotionally powerful analysis. Moving from Bugs Bunny to Playboy Bunnies, Flashdance to Frozen, the progressive '70s through the backlash '80s, the glib '90s, and the pornified aughts–and at stops in between–she explains how growing up in the shadow of "the girl" taught her to think about herself and the world and what it means to raise a daughter in the face of these contorted reflections. In the tradition of Roxane Gay, Rebecca Solnit, and Susan Sontag, Chocano brilliantly shows that our identities are more fluid than we think, and certainly more complex than anything we see on any kind of screen."–Page 4 of cover.
Section: xxvi, 275 pages : illustration ; 21 cm
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; com5170; communication; cours; discipline; discours dominant; féminisme pop; histoire et politique; journalisme; premier cycle; périodes historiques; représentation des femme*; sofia; systèmes d'oppressions; thématiques

Radical gestures: feminism and performance art in North America - Wark, Jayne (McGill-Queen's University Press, 2006)
Wark brings together a wide range of artists, including Lisa Steele, Martha Rosler, Lynda Benglis, Gillian Collyer, Margaret Dragu, and Sylvie Tourangeau, and provides detailed readings and viewings of individual pieces, many of which have not been studied in detail before. She reassesses assumptions about the generational and thematic characteristics of feminist art, placing feminist performance within the wider context of minimalism, conceptualism, land art, and happenings
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; art contemporain; art féministe; arts; corps; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; militance; performance; premier cycle; périodes historiques; régions géographiques; thématiques